Subacromial injection failure in shoulder impingement: is somatic amplification the missing link? - Bucak, Ömer Faruk; Cengiz Çavuşoğlu, Emine; Öncel, Adil; Kalaoğlu, Eser (The European Research Journal, 2025)
Objectives: To investigate whether somatosensory amplification - a heightened sensitivity to normal bodily sensations - affects the clinical response to corticosteroid injection in shoulder impingement syndrome (SIS) patients who did not respond to conservative treatment. Methods: This prospective observational study included 70 patients with SIS and persistent pain despite at least four weeks of physical therapy and non-steroidal anti-inflammatory drugs (NSAIDs). All patients received a standardized corticosteroid injection into the subacromial space under ultrasound guidance. Pain intensity was measured using the Visual Analog Scale (VAS) at rest (VAS-rest) and during movement (VAS-movement), while shoulder-related disability was assessed with the Shoulder Pain and Disability Index (SPADI) at baseline and one month after the injection. Somatosensory amplification - referring to increased sensitivity to normal bodily sensations—was evaluated using the Somatosensory Amplification Scale (SSAS), a brief self-report questionnaire administered at the one-month follow-up by a psychiatrist blinded to clinical outcomes. Treatment response was defined as a ≥30% reduction in VAS-movement, based on the minimal clinically important difference (MCID). Patients were categorized as responders or non-responders accordingly. Results: Thirty (42.9%) patients were classified as responders and 40 (57.1%) as non-responders. At 1-month, non-responders had significantly higher SSAS scores than responders (30.7 [27.4-32.6] vs. 21.5 [19.4-23.4], P